Elaboration and Use of Communication Media in Teaching and Learning The Arabic Language for Foreigners | اندماج وسائل الاتصال واستخدامه في تعليم وتعلم اللغة العربية للناطقين بغيرها - Ahmed Safidin (Al-Zahra : Journal for Islamic and Arabic Studies, 2020)
This paper addresses the issue of teaching and learning the Arabic language for non-native speakers through its focus on an integrated vision of the means of communication. Through the descriptive method the process of employing communication techniques in teaching and learning the Arabic language for non-native speakers through three topics. The first topic deals with teaching and learning the Arabic language for non-native speakers, and the second topic deals with the employment and use of communication methods in this matter, and the third topic is a vision on strengthening the relationship between Sudan and the Republic of Indonesia, through the establishment of a Sudanese Center for Distance Education to spread the Arabic language and Islamic sciences.The paper concluded that the adoption of audio and visual laboratories in teaching Arabic in various stages of study, in addition to traditional methods, can create an attractive environment to contribute to teaching the Arabic language for non-native speakers and upgrade the skills of Arabic writing by adopting the concept of paper and network research. The research analysis relied on some primary references and secondary sources, which were available to the researcher.This research is distinguished from other previous research in a number of points. One of them is the ground on which the researcher relies on the specialization in the field of media, as he addresses the issue of the Arabic language from several approaches that combine education, media and linguistics to achieve the goals of the research within the framework of knowledge integration between science.